Social Capital and Posttraumatic Growth of Students with Acquired Visual Impairment in Japanese Schools for the Blind - Erika Matsuda; Hisae Miyauchi (MDPI AG, 2023)
The induction of posttraumatic growth (PTG) is important for realizing the reintegration of people with acquired visual impairment to society. In Japan, many of these individuals receive education at schools for the blind as enrolled students. The purpose of this study was to examine the relationship between cognitive and structural social capital at schools for the blind and the PTG of students with acquired visual impairment. A questionnaire survey was conducted among students enrolled in vocational courses at schools for the blind throughout Japan. The results of the analysis of data from a sample of 255 students indicated that cognitive social capital with peers and teachers and structural social capital indicated by the frequency of participation in school club activities and interaction with local people were positively related to PTG. The findings highlight that social capital at schools for the blind are associated with markers of PTG in students with acquired visual impairment. Moreover, the findings highlight the value of schools for the blind with regards to the social participation of students with acquired visual impairment.